Whispered Words in Bella Coola: Fact vs Fiction - Nater, Hank (Journal of Language Research, 2024)
A few assertions made by Gloria Mellesmoen (2021) in an Optimality Theory-based article on obstruent clustering in Bella Coola (Nuχalk) are disputed. At issue are: (i) failure to cite all-stop and all-fricative words; (ii) exclusion of stops as potential nuclei and ambiguous views on the status of affricates; (iii) absence of a procedure to determine nuclearity of fricatives in certain environments. It is also shown that (iv) obstruent clustering is an areal trait shared with Rivers Inlet (Oowekyala). Agreeing with Newman (1947), I maintain that Bella Coola is non-syllabic.
Keywords: Bella Coola; syllabicity; Good Enough Nucleus Hypothesis; diachrony; areal features